2019
DOI: 10.1111/jog.13987
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of a new telephone consultation service for prenatal and postnatal health care

Abstract: Aims In October 2017, the ‘Prenatal and Postnatal Health Care Service in Nara (PPHSN)’ has piloted the introduction of a new telephone consultation service to support prenatal and postnatal health care and childcare. This study aimed to document the feasibility, acceptability and satisfaction with the service provided by a trained nurse specialist who can access to clinician support when necessary. Methods The pilot study was conducted between November 2017 and February 2018. Japanese women who are undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
1
11
0
2
Order By: Relevance
“…6 Medical hotlines had been set up to tackle out-of-hours services, serving as a triaging service for either urgent emergency hospital review or scheduled community appointments. 15 Secondary and tertiary care clinics had also started to integrate telephone consultation services, 1619 as demonstrated by specialist nurse-led post-natal care and prostate cancer follow-up clinics. 17,19 Additionally, a respiratory medicine clinic demonstrated similar 21-point Medical Interview Satisfaction Scale satisfaction scores from both telephone and traditional face-to-face consultations, citing the lack of travelling and waiting time as major advantages for the participating patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Medical hotlines had been set up to tackle out-of-hours services, serving as a triaging service for either urgent emergency hospital review or scheduled community appointments. 15 Secondary and tertiary care clinics had also started to integrate telephone consultation services, 1619 as demonstrated by specialist nurse-led post-natal care and prostate cancer follow-up clinics. 17,19 Additionally, a respiratory medicine clinic demonstrated similar 21-point Medical Interview Satisfaction Scale satisfaction scores from both telephone and traditional face-to-face consultations, citing the lack of travelling and waiting time as major advantages for the participating patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 Secondary and tertiary care clinics had also started to integrate telephone consultation services, [16][17][18][19] as demonstrated by specialist nurse-led post-natal care and prostate cancer follow-up clinics. 17,19 Additionally, a respiratory medicine clinic demonstrated similar 21-point Medical Interview Satisfaction Scale satisfaction scores from both telephone and traditional face-to-face consultations, citing the lack of travelling and waiting time as major advantages for the participating patients. 13 Telephone consultations have proven to be acceptable and sometimes desirable alternatives to out-patient visits, with positive satisfaction scores and safe levels of care maintained.…”
Section: Telephone Consultation Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…In Hong Kong, nurse researchers conducted health outcome studies to provide evidence for the government to make policies on smoking cessation (Chan, Leung, et al, 2011). In Japan, through health outcome studies, nurse researchers reported positive health outcomes due to the use of nurse practitioners (Kobayashi & Sado, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Bu yöntemlere örnek olarak Japonya'da doğum öncesi ve doğum sonrası sağlık hizmetleri için yeni bir telefon danışma servisi geliştirilmiştir ve ücretsiz bir cep telefonu numarası verilmiş ve bu numaradan anne ve yeni doğan bakımı uygulamalarında danışmanlık almak üzere eğitimli bir hemşireye ulaşmaları sağlanmıştır (15). Proje ayrıca çocuk yetiştirmeyi desteklemek için bilgi de sağlamıştır.…”
Section: Doğum Sonu Dönemde Teknoloji Kullanımıunclassified